The Influence Of Personality Traits And Self-Congruity On Customer Satisfaction And Brand Loyalty At El's Coffee In Bandar Lampung - SARITA, Rahma; BANGSAWAN, Satria; PANDJAITAN, Dorothy RH (International Journal of Environmental, Sustainability, and Social Science, 2024)
The development of the lifestyle of consumingcoffee has long been a business opportunity for entrepreneurs to set up coffee shops. To complete the current understanding of the importance of coffee shop branding. This research was conducted using quantitative research. The data in this research uses primary data obtained by distributing questionnaires. The data obtained was then explained descriptively and using structural equation modeling (SEM). The population in this study were Tokopedia users, totaling 400 samples. The sampling technique is carried out using probability sampling, the type is purposive sampling. The research results show that this research supports the proposed hypothesis: (1) Personality traits have a positive and significant effect on harmony, (2) Personality traits have a positive and significant effect on customer satisfaction, (3) Personality traits have a positive and significant effect on customer satisfaction. significant impact on customer satisfaction. significant effect on consumer satisfaction, (3) Personality traits have a positive and significant effect on consumer satisfaction. positive and significant effect on brand loyalty, (4) Conformity has a positive and significant effect on customer satisfaction, (5) Conformity has a positive and significant effect on brand loyalty, (6) Customer satisfaction has a positive and significant effect on brand loyalty. From the research results, these findings confirm that coffee shop owners must be encouraged to develop brand loyalty by investing in customer satisfaction. Coffee shop managers must also try as much as possible to understand the needs and desires of their customers.